2015
DOI: 10.1016/j.exppara.2015.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Immuno-evasive tactics by schistosomes identify an effective allergy preventative

Abstract: Many chronic inflammatory diseases can be improved by helminth infection, but the mechanisms are poorly understood. Allergy and helminthiasis are both associated with Th2-like immune responses; thus, defining how infection with parasites leads to reduced allergy has been particularly challenging. We sought to better understand this conundrum by evaluating host-parasite interactions involved in Th2 immunity in human schistosomiasis. Immune cells were cultured with schistosomes and the effect on CD23, an IgE rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 63 publications
0
22
0
Order By: Relevance
“…CsVAL has also displayed inhibitory activity on IgE-mediated degranulation of mast cells via targeting downstream pathways ( 156 ). Prevention of IgE receptor signaling has also been observed during exposure of human PBMCs to S. mansoni ( 158 ). It was revealed that the worm is able to secrete a component termed as schistosome-generated (SG) sCD23 which not only functions as a soluble decoy for the IgE receptor but also decreases the expression of this receptor ( 158 ).…”
Section: Helminth-derived Products (Hdps) As Potent Immunomodulatorsmentioning
confidence: 96%
“…CsVAL has also displayed inhibitory activity on IgE-mediated degranulation of mast cells via targeting downstream pathways ( 156 ). Prevention of IgE receptor signaling has also been observed during exposure of human PBMCs to S. mansoni ( 158 ). It was revealed that the worm is able to secrete a component termed as schistosome-generated (SG) sCD23 which not only functions as a soluble decoy for the IgE receptor but also decreases the expression of this receptor ( 158 ).…”
Section: Helminth-derived Products (Hdps) As Potent Immunomodulatorsmentioning
confidence: 96%
“…The Sm‐p80 protein plays an important role in the surface membrane biogenesis and turnover, a process utilized by hemo‐helminths to escape host immune responses . Sm‐p80 is also implicated in additional immune‐evasion tactics utilized by the parasite, including cleavage of the host CD23, as well as degradation of fibronectin to inhibit blood clot formation around the worm in vivo …”
Section: Introductionmentioning
confidence: 99%
“…22 The Sm-p80 protein plays an important role in the surface membrane biogenesis and turnover, a process utilized by hemo-helminths to escape host immune responses. 22 Sm-p80 is also implicated in additional immune-evasion tactics utilized by the parasite, including cleavage of the host CD23, 23 as well as degradation of fibronectin to inhibit blood clot formation around the worm in vivo. 24 The present study reports the vaccine efficacy of Sm-p80 with a Toll-like receptor 4 agonist-based adjuvant, glucopyranosyl lipid A in an oil-in water emulsion (GLA-SE), 25 in four independent doubleblind experiments with 40 baboons.…”
Section: Introductionmentioning
confidence: 99%
“…One of the reasons for this slow progress in developing an effective schistosome vaccine is due to the inherent capability of the parasites to effectively evade their host’s defensive immune responses [33;34]. Nonetheless, in three separate meetings, sponsored by the National Institute of Allergy and Infectious Diseases (NIAID) i and the Bill & Melinda Gates Foundation ii , the role of a schistosomiasis vaccine and other tools in context of schistosomiasis control and elimination strategies were discussed.…”
Section: Introductionmentioning
confidence: 99%